2020
DOI: 10.1016/j.jcta.2019.105204
|View full text |Cite
|
Sign up to set email alerts
|

Chordality, d-collapsibility, and componentwise linear ideals

Abstract: Using the concept of d-collapsibility from combinatorial topology, we define chordal simplicial complexes and show that their Stanley-Reisner ideals are componentwise linear. Our construction is inspired by and an extension of "chordal clutters" which was defined by Bigdeli, Yazdan Pour and Zaare-Nahandi in 2017, and characterizes Betti tables of all ideals with linear resolution in a polynomial ring.We show d-collapsible and d-representable complexes produce componentwise linear ideals for appropriate d. Alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Recently, Bigdeli and Faridi gave a connection between the d-collapsibility and the chordal complexes; and proved that d-collapsibility is equivalent to the chordality of the Stanley-Reisner complexes of certain ideals [11]. For applications regarding Helly-type theorems, see [9,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Bigdeli and Faridi gave a connection between the d-collapsibility and the chordal complexes; and proved that d-collapsibility is equivalent to the chordality of the Stanley-Reisner complexes of certain ideals [11]. For applications regarding Helly-type theorems, see [9,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…This class has been studied in [8]. Later, in [7] a modification of this variation of chordality was studied for simplicial complexes. Trying to compare the properties of chordal clutters and simplicial clutters, it turns out that, like chordal clutters, the ideal associated to a simplicial clutter has linear resolution over all fields and all of its graded Betti numbers can be identified explicitly (Corollary 3.1).…”
Section: Introductionmentioning
confidence: 99%
“…The above definition was introduced by Hoefel and Mermin in [25] Herzog and Hibi [27] showed that all Gotzmann ideals are componentwise linear, and Bigdeli and Faridi [11] established a connection between square-free Gotzmann and Stanley-Reisner ideals of chordal complexes -a large class of componentwise linear ideals which can be defined via simplicial collapses. Open questions that arise from this are the following: Question 2.13.…”
Section: Introductionmentioning
confidence: 99%